Mitochondrial Translation Inhibition Uncovers a Critical Metabolic–Epigenetic Interface in Renal Cell Carcinoma - Kazumi Eckenstein; Beyza Cengiz; Matthew E. K. Chang; Jessie May Cartier; Mark R. Flory; George V. Thomas (Metabolites, 2025)
Background/Objectives: Renal cell carcinoma (RCC) exhibits distinctive metabolic vulnerabilities that may be therapeutically targeted. This study investigates how tigecycline, an FDA-approved antibiotic that inhibits mitochondrial translation, affects RCC cells and explores potential combinatorial approaches to enhance its efficacy. Methods: We employed comprehensive metabolomic profiling, subcellular proteomics, and functional assays to characterize the effects of tigecycline on RCC cell lines, patient-derived organoids, and xenograft models. The synergistic potential of tigecycline with the histone deacetylase inhibitor entinostat was evaluated using combination index analysis. Results: Tigecycline selectively inhibited mitochondrial translation in RCC cells, reducing mitochondrially-encoded proteins while sparing nuclear-encoded components, profoundly disrupting mitochondrial bioenergetics and reducing tumor growth in xenograft models. Subcellular proteomic analyses revealed that tigecycline treatment triggered a significant accumulation of multiple histone variants concurrent with cell cycle arrest. Based on this discovery, combined treatment with tigecycline and entinostat demonstrated remarkable synergism across RCC cell lines and patient-derived. Conclusions: Our findings identify a promising therapeutic opportunity by targeting the crosstalk between mitochondrial function and epigenetic homeostasis in RCC, with the potential for rapid clinical translation given the established pharmacological profiles of both agents.